Judaistyczne tło Modlitwy Pańskiej (Mt 6,9-13) w świetle idei ojcostwa Bożego w Kazaniu na Górze - Rosik, Mariusz (Verbum Vitae, 2011)
The idea of God’s fatherhood seems very obvious in the Sermon on the Mount. Jesus presents God as the Father who wants all what is good for all His children and invites all His children for a deep, spontaneous and intimate relationship with Him. The idea of God’s fatherhood is present especially in the prayer which Jesus taught His disciples. The “Our Father” is a Christian prayer but it has Jewish roots. Jesus was a Hebrew and prayed according to Jewish faith. The structure of “Our Father” is as follows: invocation followed by seven requests. The contents of the prayer reveal many references to Jewish prayers, known already at the time of Jesus (Abinu malkenu, Kaddish, Shemoneh Esreh). The similarities between “Our Father” and various prayers of the Jews do not exclude uniqueness of the prayer which Jesus taught His disciples. The idea of God’s fatherhood is present also in other parts of the Sermon on the mountain: the blessings of the peacemakers (Mt 5,9), the role of the disciples (Mt 5,13-16), love for enemies (Mt 5,43-45); the call to follow Christ (Mt 5,48); the Father who sees in secret (Mt 6,1-6.1618); Father’s forgiveness (Mt 6,14-15); Father’s care (Mt 6,25-34); Father’s goodness (Mt 7,7-11) and God’s fatherly will (Mt 7,21). All these passages, just like the prayer “Our Father”, underline the importance of filial trust in God as the Father.